Teenagers’ Interest In Property Ownership In Digital Age - Windarsari, Wiwin Riski; Rostina (Abadi Institute, 2025)
This qualitative study explores the nature and drivers of property ownership aspirations among teenagers (aged 15-19) in Makassar, Indonesia, within the context of pervasive digital immersion. Adopting a phenomenological approach, data was gathered through in-depth interviews and focus group discussions with 30 participants across diverse socioeconomic backgrounds. The findings illustrate that even with significant involvement in digital technologies, teenagers mainly perceive property as a form of tangible security and a legacy to pass down through generations, highlighting persistent cultural values related to family stability. Digital platforms open up access to property information and elevate aspirations through inspiring stories, but they also heighten anxieties with unrealistic depictions of wealth and obscure practical routes to ownership. Motivations centered on independence, stability, and social validation are tempered by perceived insurmountable financial barriers rising property prices, complex financing, and cultural aversion to debt. The study concludes that teenagers navigate a disconnect between digitally fueled dreams and tangible attainability, epitomized by the metaphor “groping in the dark while holding a bright phone”. This underscores an urgent need for context-sensitive interventions leveraging digital tools for financial literacy, demystifying acquisition processes, and fostering collaborative support systems among educators, policymakers, and communities to bridge aspiration and reality.